Femoral Fixation Strength as a Function of Bone Plug Length in Anterior Cruciate Ligament Reconstruction Utilizing Interference Screws - Light, Jonathan J.; Firoved, Amanda B.; Rocchi, Vanna J.; Wellman, Laurie L.; Bonner, Kevin F. (The Journal of Knee Surgery, 2023)
Purpose To determine femoral construct fixation strength as bone plug length decreases in anterior cruciate ligament reconstruction (ACLR).Methods Sixty fresh-frozen bone–patellar tendon–bone allografts were utilized and divided into 20-, 15-, and 10-mm length bone plug groups, subdivided further so that half utilized the patella side (P) for testing and half used the tibial side (T). Ten mm diameter recipient tunnels were created within the anatomic anterior cruciate ligament footprint of 60 cadaveric femurs. All bone plugs were 10 mm in diameter; grafts were fixed using a 7 × 23 mm metal interference screw. An Instron was used to determine the load to failure of each group. A one-way multivariate analysis of variance (MANOVA) was conducted to test the hypothesis that there would be one or more mean differences in fixation stability between 20- or 15-mm plug lengths (P or T) versus 10 mm T plug lengths when cross-compared, with no association between other P or T subgroups.Results The mean load to failure of the 20 mm plugs (20 P + T) was 457 ± 66N, 15 mm plugs (15 P + T) was 437 ± 74N, and 10 mm plugs (10 P + T) was 407 ± 107N. There was no significant difference between P + T groups: 20-versus 15-mm (p = 1.000), 15-versus 10-mm (p = 0.798), and 20-versus 10-mm (p = 0.200); P + T MANOVA (p = 0.291). Within groups, there was no significant difference between patella and tibial bone plug subgroups with a pullout force range between 469 ± 56N and 374 ± 116N and p-value ranging from p = 1.000 for longer bone plugs to p = 0.194 for shorter bone plugs; P versus T MANOVA (p = 0.113).Conclusion In this human time zero cadaver model, there was no significant difference in construct failure between 20-,15-, and 10-mm bone plugs when fixed with an interference screw within the femoral tunnel, although fixation strength did trend down when from 20- to 15- to 10-mm bone plugs.Clinical Relevance There is a balance between optimal bone plug length on the femoral side for achieving adequate fixation as well as minimizing donor site morbidity and facilitating graft passage in ACLR. This study reveals utilizing shorter plugs with interference screw fixation is potentially acceptable on the femoral side if shorter plugs are harvested.
Keywords: anterior cruciate ligament reconstruction; bone–patellar tendon–bone; interference screw fixation; femoral tunnel